2018
DOI: 10.1177/0013916517751009
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Urban Nature and Tree Planting Are Related to Pro-Environmental Behavior via Connection to Nature, the Use of Nature for Psychological Restoration, and Environmental Attitudes

Abstract: Pro-environmental behaviors (PEBs) may be associated with a personal relationship with nature. We conducted a quasi-experiment with 423 residents who had or had not actively participated in a tree-planting scheme and lived in 20 neighborhoods that differ in their greenness level. We tested whether exposure to nature (specified by the amount of vegetation cover in residents’ neighborhoods) and/or past PEB (specified by tree-planting participation) was associated with residents’ PEB and whether key psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
146
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 48 publications
13
146
2
2
Order By: Relevance
“…A new and innovative line of research about the promotion of PEB draws on the hypothesis that direct contact with nature is positively associated with pro-environmental attitudes and PEB (Larson et al, 2011a; Chawla and Derr, 2012; Cheng and Monroe, 2012; Collado et al, 2015; Otto and Pensini, 2017; Whitburn et al, in press). In line with this, it has been suggested that reducing opportunities to have contact with nature can lead to an amplified feeling of human-nature dissociation (Chawla and Derr, 2012), which may, in turn, hinder support for environmental causes (Soga and Gaston, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A new and innovative line of research about the promotion of PEB draws on the hypothesis that direct contact with nature is positively associated with pro-environmental attitudes and PEB (Larson et al, 2011a; Chawla and Derr, 2012; Cheng and Monroe, 2012; Collado et al, 2015; Otto and Pensini, 2017; Whitburn et al, in press). In line with this, it has been suggested that reducing opportunities to have contact with nature can lead to an amplified feeling of human-nature dissociation (Chawla and Derr, 2012), which may, in turn, hinder support for environmental causes (Soga and Gaston, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive and robust research literature identifying the link between positive experiences in nature and PEB (Chawla and Derr, 2012), the processes behind this relation are still unclear (Wells and Lekies, 2006; Schultz and Kaiser, 2012; Whitburn et al, in press). Explanations have been offered to understand the relation between experiences in nature and PEB, such as psychological restoration (Byrka et al, 2010) and environmental attitudes (Wells and Lekies, 2006; Collado et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Available evidence suggests that life course experience with (and early perceptions of) nature can shape nature relatedness and pro-environmental attitudes/behaviors; researchers are looking more closely to determine how and in what environments nature relatedness and other 'planetary health' attitudes are shaped and how they subsequently determine interactions with nature [139][140][141][142][143][144]. Emerging research shows that understanding specific types of human-nature relationships may help predict pro-environmental behaviors [145] and the messaging that might resonate with specific groups (for example, on reducing meat consumption, one of planetary health's already-stated goals) [146].…”
Section: Moving Upstream-the Psyche Of Planetary Healthmentioning
confidence: 99%